Extraction and characterization of starch from mango seeds - Ahmad A. Shahrim, Nur’Aishah; Sarifuddin, Norshahida; Ismail, Hanafi (Institute of Physics Publishing, 2018)
The mango (Mangifera indica) seed starch were extracted via distillation, alkaline, sedimentation and centrifugation method. The effects of extraction methods on its morphology, structural and physicochemical properties extracted were comparatively studied. Morphological characteristics like shape and size of the starch granules, display significant differences under scanning electron microscope (SEM). The extracted mango seed starch granules showed oval and irregular or cuboidal-shaped with smooth surface despite of different extraction method. Distillation method yields smallest (13.80 ± 2.90 µm) starch granules in size, followed by alkaline method (15.83 ± 3.65 µm), sedimentation method (15.97 ± 4.44 µm) and centrifugation method (19.91 ± 6.82 µm). X-ray diffraction pattern whereas, showed the isolated mango seed starch is an A-type starch, hence, corroborated to suggest the morphology of the starch granules by their size. Moreover, starch isolated via alkali method had highest starch yield of 91.72 % than starch isolated via distillation (81.87 %), sedimentation (74.82 %) and centrifugation (74.56